Saint Augustine - Remond-Dalyac, Emmanuelle (Bayard, 2011)
Augustine lived over 1500 years ago, but he is still one of the great teachers about God. It took him many years to find God. When he became a Christian, Augustine had to change the way he lived, and that isn't easy. Following God's way turned out to be full of surprises!